PERTANGGUNGJAWABAN PIDANA TERHADAP KELALAIAN ORANG TUA MENGAWASI ANAK YANG MENJADI KORBAN KECELAKAAN LALU LINTAS - Meta Permata Sari; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Traffic accidents that often occur are caused by several factors, one of which is negligence, both driver and pedestrian negligence. Accident victims do not know the age from children to adults. Children who are victims of traffic accidents are mostly motivated by the negligence of parents watching their children when they are around the highway that causes children to become victims in traffic accidents.The purpose of this thesis research is first to find out the criminal liability of parents for negligence in supervising children who are victims of traffic accidents, secondly to find out the ideal idea of criminal liability for parental negligence. The type of research the author uses is normative legal research or better known as legal research.From the results of the research problem there are two main things that can be concluded. First, criminal liability for negligence in Article 359 of the Criminal Code does not specifically regulate negligence of parents towards children specifically. Positive law needs to be done about renewal of negligence of parents watching over children who become victims and die. Apart from the driver's mistake, negligence of the parents is a major factor in the traffic accident. Second, the ideal idea of criminal liability in the form of new regulations regarding the responsibilities of parents towards children is discussed in detail so that no more similar cases occur in children. Criminal fines can be applied as punishment to parents. Apart from the grieving parents lost their children's lives and then must be responsible with the criminal fines that must be paid, this aims so that the deterrent effect and the reduction of cases like this against children in the future. Author's suggestion, First, it is hoped that legal reforms need to be carried out so that law enforcement and legal protection are carried out more specifically and specifically so that parents understand their responsibilities towards children who naturally need family protection and supervision, especially parents, not necessarily forgetting their mistakes because of neglect. responsible. Secondly, the increasing number of traffic accidents and one of them is because negligence demands that we carry out a more optimal legal policy for road users both motorists and pedestrians to be more careful and especially for parents who bring their children to pay more attention to their children so that they cannot be separated from surveillance and becoming a victim of an accident.Keywords: Negligence - Responsibility of Parents - Children - Accidents